Colonization of a host tree by herbivorous insects under a changing climate. Issue 8 (4th December 2014) - Heimonen, Kaisa; Valtonen, Anu; Kontunen‐Soppela, Sari; Keski‐Saari, Sarita; Rousi, Matti; Oksanen, Elina; Roininen, Heikki
<x xml:space="preserve">Abstract</x> Climate warming has been predicted to increase the abundance of herbivorous insects. Together with concurrent poleward shifts in many insect species this may increase herbivore pressure on plants. However, the manner in which plants at higher latitudes become colonized by herbivorous insects in the future is unknown. We established a translocation experiment using 26 micropropagated silver birch Betula pendula genotypes from six populations originating from 60°N to 67°N, to study the susceptibility of the translocated birches to local herbivores. The birches were planted at three different latitudes in Finland (60°N, 62°N and 67°N). We studied the effect of source population and latitudinal translocation on herbivore density, species richness, and community composition among the genotypes growing in the same environmental conditions in two years; 2011 and 2012. The source population explained the variation in the herbivore density only in 2012, whereas latitudinal translocation did not affect herbivore density. Variation in species richness was not explained by the source population or by the latitudinal translocation. At two of the study sites, the similarity of the herbivore communities among the populations decreased with increasing latitudinal distance of the source populations, possibly because birch populations that grow geographically closer to each other are genetically more similar, and therefore support a more similar composition of the arthropod community. All birch genotypes were colonized by local herbivores, suggesting that as herbivores shift their ranges polewards, they are able to colonize novel host‐plant genotypes. This enables compositional changes in insect communities on their host plants in the future, which in turn, might affect total herbivory and eventually, plant growth.